Bioanalytical method development, in-vivo pharmacokinetic evaluation, ex-vivo platelet aggregation inhibition activity of a novel solid dispersion formulation of ticagrelor - Srivastava, Abhishek; Bedi, Simrata; Mehata, Abhishesh Kumar; Pawde, Datta Maroti; Hatware, Ketan Vinayakrao; Khan, Mohammad Ahmad; Muthu, M. S.; Bhandari, Uma (Frontiers in Medical Technology, 2025)
BackgroundTicagrelor, a potential antithrombotic drug indicated for cardiovascular events with acute coronary syndrome, has been restricted from its oral use due to poor aqueous solubility. The present investigation aimed to develop validated bioanalytical method for the analysis of plasma samples for improving the oral bioavailability of Ticagrelor. Additionally, evaluation of the improved antiplatelet activity of the Ticagrelor formulation compared to the marketed formulation.MethodsA bioanalytical method was developed in rat plasma samples using the isocratic separation mode. Plasma samples were processed by liquid-liquid extraction and analyzed by using reverse phase HPLC. A validated method was used for evaluating the pharmacokinetic profile of the developed formulation and marketed formulation in Sprague Dawley rats. Additionally, the ex-vivo antiplatelet aggregation activity was evaluated.ResultsThe developed method was accurate and linear (100 ng−800 ng) to quantify the drug in plasma. An in-vivo pharmacokinetic study was conducted for formulation at 10 mg/kg and different pharmacokinetic parameters were evaluated. From the results, we observed∼64% enhancements in the oral bioavailability of the Ticagrelor relative to the marketed formulation. The developed formulation (SD1) showed more significant inhibition of ADP-induced platelet aggregation compared to the marketed ticagrelor (RLD) formulation.ConclusionIn conclusion, we have successfully developed a validated analytical method for estimating Ticagrelor plasma concentration. Additionally, our study successfully enhanced Ticagrelor's oral bioavailability, and the developed formulation has more significant inhibition of ADP-induced platelet aggregation relative to the marketed formulation, indicating its substantial therapeutic potential.